NQO1 Binds and Supports SIRT1 Function - Tsvetkov, Peter; Adler, Julia; Strobelt, Romano; Adamovich, Yaarit; Asher, Gad; Reuven, Nina; Shaul, Yosef (Frontiers in Pharmacology, 2021)
Silent information regulator 2-related enzyme 1 (SIRT1) is an NAD+-dependent class III deacetylase and a key component of the cellular metabolic sensing pathway. The requirement of NAD+ for SIRT1 activity led us to assume that NQO1, an NADH oxidoreductase producing NAD+, regulates SIRT1 activity. We show here that SIRT1 is capable of increasing NQO1 (NAD(P)H Dehydrogenase Quinone 1) transcription and protein levels. NQO1 physically interacts with SIRT1 but not with an enzymatically dead SIRT1 H363Y mutant. The interaction of NQO1 with SIRT1 is markedly increased under mitochondrial inhibition. Interestingly, under this condition the nuclear pool of NQO1 is elevated. Depletion of NQO1 compromises the role of SIRT1 in inducing transcription of several target genes and eliminates the protective role of SIRT1 following mitochondrial inhibition. Our results suggest that SIRT1 and NQO1 form a regulatory loop where SIRT1 regulates NQO1 expression and NQO1 binds and mediates the protective role of SIRT1 during mitochondrial stress. The interplay between an NADH oxidoreductase enzyme and an NAD+ dependent deacetylase may act as a rheostat in sensing mitochondrial stress.